contestada

How do you prove this trig identity?

[tex] \frac{{sec}^{2} \theta - 1}{ {sec}^{2} \theta } = {sin}^{2} \theta[/tex]

Respuesta :

On the left side, multiply numerator and denominator by [tex]\cos^2\theta[/tex]:

[tex]\dfrac{\sec^2\theta-1}{\sec^2\theta}=\dfrac{\cos^2\theta(\sec^2\theta-1)}{\cos^2\theta\sec^2\theta}=\dfrac{1-\cos^2\theta}1[/tex]

which follows from the fact that [tex]\sec\theta=\dfrac1{\cos\theta}[/tex]. Then apply the Pythagorean identity,

[tex]\sin^2\theta+\cos^2\theta=1\implies\dfrac{\sec^2\theta-1}{\sec^2\theta}=\sin^2\theta[/tex].

and we're done.

ACCESS MORE